O bem-estar de homossexuais: associações com o apoio social familiar, resiliência, valores e religiosidade - Campos, Lais Sudré (2015)
This dissertation aims at investigating the associations between the homosexuals’ wellbeing and the familiar social support, resilience process, evaluative priorities and religiosity level. To reach this goals, we conducted two studies. The first study aims at empirically investigating the association between the familiar social support and the homosexuals’ well-being, as well as other relevant constructs for the higher or lower level of social support, such as family religiosity and prejudice. The subjects of this study were 20 male and female homosexuals, 10 each, living at Vitória/ES, which ages varied between 19 e 27 years old (M=22,70; DP=2,47). The subjects responded to an individual semi-structured interview that was analyzed based on the content analysis technique. The principal result was the evidences of a familiar adjustment model to the homosexual members, from the coming out until the possible family acceptance, including the consequences of the lack of support on homosexuals’ well-being and the media and religion as complicating factors of this process. The second study aims to assess the religiosity, social support, resilience and values constructs and to investigate if they can be considered risk or protection factors to the homosexuals’ well-being. Furthermore, the study aims at presenting the correlations between these constructs, as well as evidences of validity adaptation of the Brief Resilience Scale and the Perceived Parental Support Scale – Lesbian/Gay to the Brazilian context. To reach this goals, we analyzed the answers of 229 Brazilian homosexuals, mostly women (58,5%), with aging varying from 18 to 61 years old (M=24,02; DP=5,98), to a questionnaire containing sociodemographic questions and the scales: Escala de Bem-estar Subjetivo (Subjective Well-Being Scale), Escala de Resiliência Breve (Brief Resilience Scale), Questionário dos Valores Básicos (Basic Values Questionnaire), Escala de Apoio Social Familiar Percebido – Lésbica/Gay (Perceived Parental Support Scale – Lesbian/Gay), Inventário de Percepção de Suporte Familiar (Family Support Perception’s Inventory) and WHOQOL-SRPB. The main results point to the scales’ validation evidences; the correlation between familiar social support, resilience and some values as religiosity; and the majority presence of familiar social support, resilience, religiosity and interactional values among the homosexuals’ well-being predictors; and family inadequacy, realization values and the religiosity factor “admiration” among the homosexuals’ well-being risky factors. As a dissertation’s general result, we point to the importance of social support in the fight against prejudice, the resilience needed to overcome these difficulties, the values associated with the way homosexuals face these situations and the religiosity acting toward a source of peace and hope to overcome the difficulties, confirming the associations between all the investigated constructs with the homosexuals’ well-being.